1971
DOI: 10.1039/tf9716700500
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of n-fatty acids at the silica/benzene and silica/n-hexane interface. Part 2.—Heats of adsorption

Abstract: The heats of (selective) adsorption of the n-C6, C,, CIz, CI4 and c 1 6 fatty acids at tlic silica/ benzene interface have been determined from measurements of the heats of immersion of " fully " hydroxylated silicas in benzene + n-fatty acid solutions. Within experimental error, the molar heat of adsorption is independent both of the surface coverage of the fatty acids and of their hydrocarbon chain length. The heats of solution of the fatty acids in benzene at 27°C have also been measured and indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…versus concentration. Calorimetric data at 27°C for the adsorption of n-fatty acid from benzene solution on silica indicates the adsorption to be independent of surface coverage and chain length [277]. It was further postulated that the expected decrease in heat of adsorption due to adsorbateadsorbent interaction is offset by a decreasing enthalpy of mixing of the adsorbed film.…”
Section: Thermodynamics Of Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…versus concentration. Calorimetric data at 27°C for the adsorption of n-fatty acid from benzene solution on silica indicates the adsorption to be independent of surface coverage and chain length [277]. It was further postulated that the expected decrease in heat of adsorption due to adsorbateadsorbent interaction is offset by a decreasing enthalpy of mixing of the adsorbed film.…”
Section: Thermodynamics Of Adsorptionmentioning
confidence: 99%
“…It was further postulated that the expected decrease in heat of adsorption due to adsorbateadsorbent interaction is offset by a decreasing enthalpy of mixing of the adsorbed film. Heats of adsorption of benzene, pyridine, and furan on to silica were measured calorimetrically [276][277][278][279][280]. Much work has been devoted to the development of infra red spectroscopy as an indirect method of determining heats of adsorption on silica including aromatics from both the liquid [281][282][283] and gas [279,280,[284][285][286].…”
Section: Thermodynamics Of Adsorptionmentioning
confidence: 99%
“…Earlier results on the change in max of fatty acids from heptane on silica, where considerable care was taken to exclude water from the system, have shown that the extent of fatty acid adsorption decreases with increasing chain length from hexanoic to palmittic acid (15). It was concluded that this decreased adsorption could not be caused by a parallel orientation of the acid molecules on the surface and that it was probably not related to the structure of the adsorbed phase.…”
Section: Adsorption Of 4-hba From Decane On Silicamentioning
confidence: 95%
“…Armistead et al (15) and Madsen and Lind (9) used carefully dried silica mixed with dried solutions of carboxylic acids in their experiments. Results obtained by Madsen and Lind (9) indicate that there was a small but insignificant (i.e., within the error limits of the experiments) decrease in the adsorption from cyclohexane on silica when the adsorbate was changed from hexanoic (C 6 ) to benzoic (C 7 ) acid.…”
Section: Adsorption Of 4-hba From Decane On Silicamentioning
confidence: 99%
See 1 more Smart Citation